Соціально-правові аспекти формування системи попередження правопорушень серед неповнолітніх - Пінчук, Ю. К.; Pinchuk, Yu. K.; Юлія Пінчук (Право і безпека. - 2021. - № 3 (82). - С. 192-199, 2021)
Проаналізовано аспекти сучасної системи попередження правопорушень серед неповнолітніх. Визначено особливості діяльності суб’єктів профілактики правопорушень, а також надано рекомендацій щодо її поліпшення. Розглянуто питання молодіжної політики соціально-правового характеру, яке стосуються як майбутнього країни в цілому, так і кожного неповнолітнього громадянина. The state of juvenile delinquency in the state is an indicator of the development of civil society, its culture and morality. The formation of the state system of crime prevention is one of the directions of the state youth policy. In this regard, there is a need to analyze the current sociolegal aspects of the formation of a system of prevention of juvenile delinquency. The purpose of the article is an in-depth analysis of the features of the modern system of juvenile delinquency prevention, identification of the features of the activities of crime prevention entities, as well as providing recommendations for its improvement. The following methods are used in the article: dialectical method of research of legal phenomena, by means of which the peculiarities of formation of the system of crime prevention among minors are established; formal-legal method – for consideration of normative-legal acts regulating activity of subjects of preventive activity, as well as to identify gaps and shortcomings in the legal framework of the relevant activities; historical and legal – to assess the processes of formation and development of the system of prevention of juvenile delinquency. The current state of juvenile crime prevention is considered. It is noted that preventive activities are a set of socio-legal, pedagogical and cultural measures aimed at identifying and eliminating the causes that contribute to delinquency and anti-social actions of minors. It is determined that the existing system of juvenile delinquency prevention is ineffective, it has no integrity, preventive activities are not comprehensive. Emphasis is placed on the need for cooperation between all subjects of preventive activities, the direction of the system of juvenile delinquency, primarily to eliminate the causes of crime, prevention of offenses. The need to create an autonomous subsystem of juvenile courts was emphasized. Проанализированы аспекты современной системы предупреждения правонарушений среди несовершеннолетних. Определены особенности деятельности субъектов профилактики правонарушений, а также предоставлены рекомендации по ее улучшению. Рассмотрены вопросы молодежной политики социально-правового характера, касающиеся как будущего страны в целом, так и каждого несовершеннолетнего гражданина.
Socio-legal aspects of formation of the system of prevention of offenses among minors
Социально-правовые аспекты формирования системы предупреждения правонарушений среди несовершеннолетних
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; злочинність неповнолітніх; преступность несовершеннолетних; juvenile delinquency; попередження правопорушень; предупреждение правонарушений; crime prevention; ювенальна превенція; ювенальная превенция; juvenile prevention; профілактична діяльність; профилактическая деятельность; preventive activities; Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Національна поліція України. National police of Ukraine. Национальная полиция Украины; Национальная полиция Украины; National police of Ukraine; поліція; полиция; police; соціально-правові аспекти; социально-правовые аспекты; socio-legal aspects; неповнолітні; несовершеннолетние; minors